Poor patient awareness of peripheral arterial disease, it is time to optimize the clinical visit. Issue 3 (June 2022) - Keelan, Stephen; Foley, Niamh; Healy, Donagh; Kheirelseid, Elrasheid; McHugh, Seamus; Moneley, Daragh; Naughton, Peter
Abstract: Introduction: Peripheral arterial disease (PAD) is a growing public health burden. The development and progression of PAD is influenced by vascular risk factor management and lifestyle changes. However, public awareness of PAD is low compared with other conditions such as heart disease and stroke, which have been the subject of widespread public health campaigns. This study aimed to determine current levels of PAD awareness among hospital patients. Methods: This cross-sectional, tertiary hospital-based, descriptive study was conducted over 6 months in 2019. Two investigators administered the survey in face-to-face interviews to patients attending 3 different hospital-based settings including vascular clinics (VC), cardiology clinics (CVC), and Emergency Department (ED). Results: A total of 150 patients were interviewed. Participants demonstrated low overall awareness of vascular disease (32% PAD and 21% AAA) compared to cardiovascular disease including stroke (71%) and myocardial infarction (63%). Awareness of PAD was higher in vascular patients (51%) compared to CVC and ED patients (p=<0.01). Of the total population, 77% and 71% identified the contributory role of smoking and limited exercise to the development of PAD respectively. VC patients were more informed of intermittent claudication (78%) and amputation (80%) (p < 0.01) compared to CVC and ED patients. Conclusion: In the global drive to reduce vascular morbidity, this study highlights the poor knowledge of PAD among the public. In addition, there is poor awareness about the incidence, risk factors and complications of PAD. These results highlight the need for accessible and easily understood information regarding PAD in both the clinic setting and public health campaigns. Highlights: There is a significant lack of awareness of peripheral artery disease (PAD). There is poor awareness among the general public and in patients with PAD. Disease-specific knowledge deficits may have detrimental effects on disease course. It is important to maximise clinical visits to inform and educate patients. Focused awareness campaigns should fill disease-specific knowledge deficits.